(untitled) (Південний архів (історичні науки), 2023)
The research purpose is to examine specificity of occupation exemplified by Kherson during the full-scale Russian- Ukrainian war in March–November 2022. Methodological foundations of the study involve such methods as analysis, synthesis, observation, frontier, local history, everyday life and oral history. Main research results. On March 1, 2022 Kherson became the first regional center occupied after the beginning of the full-scale Russian aggression and the third one – after the beginning of the Russian-Ukrainian war in 2014. Its temporary occupation had lasted 8 months and 10 days by November 11, 2022. The examined period is characterized by capturing the regional center Kherson and its being occupied temporarily by Russian armed forces. The research makes an attempt to comprehend and outline specificity of Kherson’s being under occupation in everyday life aspects. The study suggests a periodization of the city’s temporary occupation divided into three periods: 1) transformational (March – the end of May, 2022); 2) integrational (the end of May – the beginning of October, 2022); 3) restructuring (the beginning of October – the beginning of November, 2022). Each stage had its own specificity and special contours of everyday perception of the war conflict, had its boundaries and internal logic that reflected on civilians’ psychological perception of the course of the war campaign and their expectations of liberation. The research finds out special characteristics of each period and substantiates transitions from one period to another. It suggests considering occupation of Kherson as a special type of the Russian regime’s occupation practice. The study also involves depiction of the local population’s everyday life based on oral history information and personal reflections of staying in the temporarily occupied zone. Conclusions. The conclusions determine chronological boundaries and specificity of occupation exemplified by Kherson. The research suggests and substantiates division of Kherson’s temporary occupation into three periods. The study proves impossibility to realize the aggressor’s plans concerning incorporation of Kherson into Russian federation and failure of the artificial «novorossia» territory.